Severe magnesium deficiency compromises systemic bone mineral density and aggravates inflammatory bone resorption - Belluci, Marina Montosa [UNESP]; de Molon, Rafael Scaf [UNESP]; Rossa, Carlos [UNESP]; Tetradis, Sotirios; Giro, Gabriela; Cerri, Paulo Sergio [UNESP]; Marcantonio, Elcio [UNESP]; Orrico, Silvana Regina Peres [UNESP] (My University, 2020)
We sought to evaluate the effects of magnesium (Mg) intake deficiency on bone metabolism in rats with induced periodontal disease (PD). Holtzman rats were randomly divided into two groups: Control — animals fed a standard diet and test — animals fed a diet with 90% Mg deficiency. After 60 days on the diets, all animals received ligature on the lower left first molars to induce PD. Animals were euthanized after 30 days following ligature placement. Blood and urine were collected for determination of serum concentrations of Mg, calcium, osteocalcin (OCN), alkaline phosphatase and parathyroid hormone (PTH) by enzyme-linked immunosorbent assay, and the urinary concentration of deoxypyridinoline (DPD). Systemic bone mineral density (BMD), bone volume and architectural bone parameters were evaluated by micro-CT in L4 lumbar vertebrae and mandible. Tartrate-resistant acid phosphatase staining and immunohistochemical (IHC) analysis of inducible nitric oxide synthase (iNOS), Runt-related transcription factor 2 (RUNX2), CD86, CD80, proliferating cell nuclear antigen, vascular endothelial growth factor, OCN and osteopontin were investigated. Reverse-transcription polymerase chain reaction was employed to assess mRNA expression of receptor-activator of nuclear factor-kB ligand, osteoprotegerin (OPG) and interleukin (IL)-6. Mg deficiency was associated with higher concentrations of PTH and DPD, and significant decrease on both systemic and mandibular BMD, as well as greater severity of alveolar and trabecular bone loss. Significant increase in osteoclasts was observed in the test group with PD. IHC analysis showed significant increase in the expression of iNOS and decreased expression of OCN and RUNX2. Increased IL-6 mRNA and decreased OPG mRNA expressions were evidenced in the test group with PD. Mg deficiency caused systemic effects indicative of altered bone metabolism in the vertebrae and affected both immune and stromal cells, aggravating inflammatory bone resorption in the ligature-induced model of periodontitis.
Keywords: Bone resorption; Magnesium deficiency; Osteoporosis; Periodontal disease; Rats; X-ray microtomography